Effect of polarimetric nonregularity on the spin of three-dimensional polarization states. (18th June 2021) - Gil, José J; Friberg, Ari T; Norrman, Andreas; Setälä, Tero
Abstract: While the spin of two-dimensional polarization states admits a simple representation, its physical interpretation for three-dimensional (3D) mixed polarization states requires a more involved analysis. In this work, we address the spin structure of the electric field of a general 3D polarization state by taking advantage of the characteristic decomposition and the recently introduced notion of nonregularity associated with 3D states. We show that a nonregular polarization state necessarily has an additional spin component due to the state's genuinely 3D nature, and both the orientation and magnitude of the spin are regulated by the degree of nonregularity. The results provide new physical insight into partially polarized evanescent and tightly focused light fields in which strong nonregular character has recently been demonstrated.